Development of pH-responsive chitosan-based hydrogel modified with bone ash for controlled release of amoxicillin - AYCAN, DİDEM; ALEMDAR YAYLA, NESLİHAN (ELSEVIER SCI LTD, 2018)
In present study, bone ash-reinforced chitosan-based hydrogels were obtained by encapsulation of bone ash into the hydrogel structure which was fabricated by photopolymerization of chitosan-grafted-glycidyl methacrylate (CTS-g-GMA) and poly(ethylene glycol) diacrylate (PEGDA) under the UV light. Hydrogels were characterized by ATR-FTIR, SEM and XRD analyses. Mechanical performance of the hydrogels was determined by universal mechanical tester. Cytotoxicity tests for hydrogels were conducted with L929 cell lines to determine cellular compatibility. Swelling tests were carried out to investigate the water uptake capacity of hydrogels. Amoxicillin which could be used for treatment of gastric ulcer was selected as the model drug. The release of amoxicillin was provided at simulated gastric (pH: 1.2) and intestinal media (pH: 7.4) in efficient and controlled manner. All results visualized that the obtained pH-sensitive chitosan-based hydrogel with enhanced mechanical properties could be a potential candidate as a drug carrier for treatment of gastric ulcer in the future applications.
Keywords: Smart hydrogel; Chitosan; Bone ash; Controlled release; Amoxicillin; DRUG-DELIVERY; GLYCIDYL METHACRYLATE; BIOACTIVE GLASS; DEGRADATION; FABRICATION; MICROSPHERES; MORPHOLOGIES; DERIVATIVES; COMPOSITES; SCAFFOLDS